Pengembangan Strategi Pembelajaran SIRNI (Stimulation, Idea Generation, Riset, Conclusion, Reflection) Terintegrasi Laboratorium Virtual Untuk Meningkatkan Pemahaman Konsep dan Keterampilan Metakognitif Peserta Didik - Sirniawan Sirniawan; Marwidayanti Marwidayanti; Muhiddin Palennari (Universitas Nusantara PGRI Kediri, 2024)
Metacognition skills and concept understanding can be improved through learning strategies that lead to improved thinking skills. Learning strategies are used to achieve learning objectives effectively and efficiently with the help of virtual laboratories as learning media and provide opportunities to get information more efficiently, also make students aware of their thinking control, so they know what to do and how to do it and students learn to actively reconstruct their conceptual understanding. This study aims to analyse the development of virtual laboratory integrated learning strategies that can improve metacognition skills and concept understanding in biology learning. This type of research is method using the literature study method. The development of this learning strategy adapts the Inquiry, Discovery and Cooperative learning strategies to produce the SIRNI strategy. The syntax of the SIRNI learning strategy is Stimulation, Idea Generation, Research, Conclusion, Reflection This learning strategy is expected to help improve students' metacognition skills and concept understanding so that students' mastery in processing learning information increases, helps students solve problems related to misconceptions and learning errors, and increases students' desire to learn.